2021
DOI: 10.1002/sia.6985
|View full text |Cite
|
Sign up to set email alerts
|

Optical, electronic, and microstructural properties of mixed phase RF magnetron sputtered vanadium oxide thin films on quartz and aluminized quartz

Abstract: Optical, electronic, and microstructural properties of mixed phase RF magnetron sputtered vanadium oxide thin films on quartz and aluminized quartz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…This suggested that the thin-film V 2 O 5 cathodes formed by the PVD process are amorphous, regardless of the Ar pressure used. 22,25 Raman spectroscopy data further verified that no crystalline phases were present in H-V 2 O 5−x and L-V 2 O 5−x , confirming the XRD results (Figure S3b). Based on prior literature, we expect that the lack of crystalline phases in H-V 2 O 5−x and L-V 2 O 5−x would assist the Zn 2+ ion diffusion.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…This suggested that the thin-film V 2 O 5 cathodes formed by the PVD process are amorphous, regardless of the Ar pressure used. 22,25 Raman spectroscopy data further verified that no crystalline phases were present in H-V 2 O 5−x and L-V 2 O 5−x , confirming the XRD results (Figure S3b). Based on prior literature, we expect that the lack of crystalline phases in H-V 2 O 5−x and L-V 2 O 5−x would assist the Zn 2+ ion diffusion.…”
Section: Resultssupporting
confidence: 77%
“…Interestingly, X-ray diffraction (XRD) patterns of H-V 2 O 5– x and L-V 2 O 5– x showed no V 2 O 5 -related peaks, but only a peak related to the SS substrate (Figure g). This suggested that the thin-film V 2 O 5 cathodes formed by the PVD process are amorphous, regardless of the Ar pressure used. , Raman spectroscopy data further verified that no crystalline phases were present in H-V 2 O 5– x and L-V 2 O 5– x , confirming the XRD results (Figure S3b). Based on prior literature, we expect that the lack of crystalline phases in H-V 2 O 5– x and L-V 2 O 5– x would assist the Zn 2+ ion diffusion. , To investigate the elemental valence states of H-V 2 O 5– x and L-V 2 O 5– x , X-ray photoelectron spectroscopy (XPS) analysis was performed.…”
Section: Resultssupporting
confidence: 72%
“…However, the existing literature reports the occurrence of SMT at different temperatures. Despite the diversity in thickness [32] and substrates investigated, there remains a lack of clear explanation or direct correlation [4,[6][7][8][9][11][12][13][14][15][16][17][18] which demands the examination of factors influencing the SMT in V 2 O 5 . This includes understanding the SMT in different forms of vanadium oxide, such as crystalline, multilayered, doped, and composite materials.…”
Section: Introductionmentioning
confidence: 99%